Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 3 - The Derivative - 3.3 Rates of Change - 3.3 Exercises: 1



Work Step by Step

y = $x^{2}$ + 2x between x = 1 and x = 3 To find the rate of change, you have to use the rate of change formula: $\frac{f(b)-f(a)}{b-a}$ In this problem, the starting point is at 1 and the end point is 3. Therefore, a = 1 and b = 3. Knowing this, you can plug these numbers back into the formula. $\frac{(3^{2}+2\times3)-(1^{2}+2\times1)}{3-1}$ = $\frac{(9+6)-(1+2)}{2}$ = $\frac{15-3}{2}$ = $\frac{12}{2}$ = 6 Therefore, the rate of change equals 6.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.